Titanium Implants Functionalized with Zoledronic Acid Associated with Ruterpy Accelerate Peri-Implant Repair in Healthy and Osteoporotic Rats - Paludetto, Laura Vidoto [UNESP]; Breseghello, Isadora [UNESP]; Frasnelli, Sabrina Cruz Tfaile [UNESP]; de Souza Batista, Fábio Roberto [UNESP]; Botacin, Paulo Roberto [UNESP]; Silva, Cristina Antoniali [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Okamoto, Roberta [UNESP] (MDPI, 2025)
Osteoporosis compromises bone quality and impairs implant osseointegration. Since an adequate bone bed is essential for implant stability and success, this study evaluated the effects of implant surface functionalization with zoledronic acid (ZOL), alone or combined with ruterpy (TERPY), on peri-implant bone healing in healthy (SHAM) and osteoporotic (OVX) rats. ZOL has antiresorptive properties, while TERPY exhibits osteoinductive potential. The hypothesis was that ZOL + TERPY would act synergistically by inhibiting bone resorption and promoting new bone formation. Sixty-six female Wistar rats (3 months old) were divided into six groups (n = 11) according to systemic condition (SHAM or OVX) and implant type: conventional (CONV), ZOL, or ZOL + TERPY. Surgeries (sham or bilateral ovariectomy) were performed on day 0, and implants were placed in the tibial metaphysis on day 90. Fluorochromes were administered on days 104 (calcein) and 114 (alizarin), and euthanasia was performed on day 118. Samples were analyzed histologically via confocal microscopy and micro-computed tomography (Micro-CT). The ZOL + TERPY groups demonstrated significantly accelerated peri-implant bone repair, showing greater bone formation and organization; improved BV/TV, Tb.N, and I.S.; and reduced Tb.Sp and Po.Tot compared to CONV and ZOL-alone groups. In conclusion, ZOL + TERPY enhances and speeds bone healing, even under osteoporotic conditions.